Artemisinin analogue SM934 ameliorates the proteinuria and renal fibrosis in rat experimental membranous nephropathy - LI Tian-tian; ZHANG Xiao-hui; JING Jing-feng; LI Xin; YANG Xiao-qian; ZHU Feng-hua; TANG Wei; ZUO Jian-ping (Acta Pharmacologica Sinica, 2017)
Aim: SM934 is a novel water-soluble artemisinin derivative with immunoregulatory activities that has been used to treat murine lupus nephritis. In the current study, we investigated the effects of SM934 on rat experimental membranous nephropathy. Methods: Passive Heymann nephritis (PHN) was induced in SD rats by intraperitoneal injection of anti-Fx1A serum. The rats were orally administered SM934 (12.5 and 25 mg·kg-1·d-1) or prednisolone (5 mg·kg-1·d-1) for 28 d. Blood and urine sample, and kidney tissue were collected for analyses. Human complement C3a-induced injury of HK-2 cells was used for in vitro experiments. Results: Treatment of PHN rats with SM934 or prednisolone attenuated the progression of glomerulonephritis and renal fibrosis, as evidenced by the reduced level of proteinuria and circulating antibodies, as well as by the reduced immune complex deposition, reversed podocyte injuries, and attenuated tubulointerstitial fibrosis in the kidneys. Furthermore, the two drugs suppressed TGF- β1 expression and Smad2/3 phosphorylation, and increased Smad7 expression in the kidneys. The two doses of SM934 produced almost identical therapeutic effects on PHN rats. Pretreatment with SM934 or a C3a receptor antagonist blocked the C3a-induced epithelial-mesenchymal transition in HK-2 cells in vitro. Conclusion: SM934 ameliorates kidney injury and attenuates the tubulointerstitial fibrosis in PHN rats by down-regulation of the TGF- β1/Smad signaling pathway.